Growth Performance and Survival Rate of Fogera and Their Crossbred Calves at Government Ranches in Ethiopia - Gessesse, Tazeb; Dagnew, Yohannes; Abegaz, Solomon; Tesfa, Assemu (Frontiers in Animal Science, 2021)
The economic benefit of dairy production can be enhanced by increasing the efficiency of growth and survival rate of calves. The objective of the study was to evaluate the effects of non-genetic factors on pre and post weaning growth traits and mortality rate of pure Fogera and their F1 cross Fogera x Holstein Friesian calves at Andassa and Chagni cattle breeding and improvement ranch. Retrospective types of study design and direct measurement were used to collect the data. A total of 3626 for pre-weaning weight records and 107 for post-weaning measurements were used for analysis. Growth traits were analysed using General linear model (GLM) of the Statistical Analysis System (SAS 9.1) while survival traits were estimated by using cox regression and Kaplan–Meier model of Stata SE 14 software. Genotype, sex, dam parity, year of birth, season of birth and location were production factors considered. The overall least square means (LSM±SE) of birth weights were 22.33±0.12 and 24.56±0.11kg for Fogera and their crosses, respectively. The overall LSM±SE of weaning weights were 93.25±0.85kg and 111.63±0.84 kg for Fogera and their cross calves, respectively. The overall post weaning weight for Fogera and their cross calves were 101.02±1.62 and 111.08±2.65, respectively. All variables considered in the model, except dam parity, significantly (P<0.05) affect post-weaning weight. The overall recorded mortality rate was 3% which was nearly the optimum that many scholars agreed to successful rearing practices.